Charting a Course for Culturally Responsive Physical Education - Robinson, Daniel B.; Lunney Borden, Lisa; Robinson, Ingrid M. (Alberta Journal of Educational Research, 2013)
In this article, we explore the absence of understanding related to culturally responsive pedagogy in physical education for Aboriginal students. In so doing, we examine the limited literature related to culturally responsive physical education and the especially limited literature dedicated to Aboriginal students within physical education. Recognizing that this absence should present a very obvious concern for pre-service physical education teachers, in-service physical education teachers, teacher educators, and most importantly, Aboriginal students themselves, we borrow from the few most notable pedagogues who share our concern and offer a framework and suggestions for future practice and inquiry. We make these suggestions for future practice and inquiry with the wholehearted belief that a commitment to culturally responsive pedagogy can improve upon the immediate and long-term physical education experiences of Aboriginal and non-Aboriginal students. Dans cet article, nous portons notre attention sur le manque de compréhension par rapport à la pédagogie tenant compte de la réalité culturelle des élèves autochtones dans les cours d’éducation physique. Ainsi, nous étudions le nombre limité de publications qui touchent les cours d’éducation physique adaptés à la culture, et notamment celles, encore plus limitées, qui traitent de la culture autochtone. Reconnaissant que cette lacune devrait constituer une préoccupation bien évidente pour les stagiaires en éducation physique, les enseignants en éducation physique, les formateurs d’enseignants et, surtout, les élèves autochtones eux-mêmes, nous puisons chez les pédagogues importants qui partagent nos préoccupations (ils sont peu nombreux) et offrons un cadre et des suggestions pour des pratiques et des recherches futures. Nous proposons ces suggestions pour les pratiques et les études futures, sincèrement convaincus qu’un engagement visant une pédagogie adaptée à la culture peut améliorer, dans l’immédiat et à long terme, les expériences des élèves autochtones et non-autochtones dans les cours d’éducation physique.